Experimental, Spectroscopic, and Computational Insights into the Reactivity of “Methanal” with 2-Naphthylamines - Havlík, Martin (2023)
The reactions of 2-naphthylamine and methyl 6-amino-2-naphthoate with formalin and paraformaldehyde were studied experimentally, spectrally, and by quantum chemical calculations. It was found that neither the corresponding aminals nor imines were formed under the described conditions but could be prepared and spectrally characterized at least in situ under modified conditions. Several of the previously undescribed intermediates and by-products were isolated or at least spectrally characterized. First principle density functional theory (DFT) calculations were performed to shed light on the key aspects of the thermochemistry of decomposition and further condensation of the corresponding aminals and imines. The calculations also revealed that the electrophilicity of methanal was significantly greater than that of ordinary oxo-compounds, except for perfluorinated ones. In summary, methanal was not behaving as the simplest aldehyde but as a very electron-deficient oxo-compound.